Hubungan Pola Asuh Ibu dengan Status Gizi Balita 12-59 Bulan Di Kecamatan Banda Sakti - Mauliza; Harvina Sawitri; Desti, Meltri Rahma (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2023)
The nutritional status of children under five is still a challenge for all levels of society, especially health workers. Globally in 2019, around 144 million children under 5 years of age worldwide suffer from stunting, two-thirds of whom live in WHO Africa and the Southeast Asia region. The percentage of nutritional status in Indonesia, especially in Aceh, is still fluctuating. Although it has decreased to 17.7%, the percentage of nutritional status of children under five has not reached the expected target of 17%. One of the factors related to the nutritional status of children under five is the parenting style of parents, especially mothers. This study aims to determine the relationship between maternal parenting and the nutritional status of children under five in the working area of ​​the Banda Sakti Health Center. The research method used a cross-sectional design, with mothers who had toddlers aged 12-59 months as respondents. The results of the study using the chi square test showed that there was a relationship between maternal parenting consisting of feeding, environmental sanitation/hygiene, and health services with toddlers aged 12-59 months in the working area of ​​Banda Sakti Health Center, Lhokseumawe City in 2022 with p <0 ,05. The result of this study indicate that there is a relationship between maternal parenting which consists of feeding, hygiene/hygiene and environmental sanitation, and health services in the working area of ​​the Banda Sakti Public Health Center, Lhokseumawe City.